2008
DOI: 10.1103/physrevb.77.075112
|View full text |Cite
|
Sign up to set email alerts
|

Optimized norm-conserving Hartree-Fock pseudopotentials for plane-wave calculations

Abstract: We report Hartree-Fock (HF) based pseudopotentials suitable for plane-wave calculations. Unlike typical effective core potentials, the present pseudopotentials are finite at the origin and exhibit rapid convergence in a plane-wave basis; the optimized pseudopotential method [A. M. Rappe et al. , Phys. Rev. B 41 1227-30 (1990] improves plane-wave convergence. Norm-conserving HF pseudopotentials are found to develop long-range non-Coulombic behavior which does not decay faster than 1/r, and is non-local. This b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…A correction procedure is necessary to remove this tail and restore the correct long-range behavior of the pseudopotential while maintaining the eigenvalue spectrum and logarithmic derivatives. Recent work 22,26,27 has shown that this approach yields highly accurate Hartre-Fock pseudopotentials.…”
Section: Recently Wu Et Al (Wsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…A correction procedure is necessary to remove this tail and restore the correct long-range behavior of the pseudopotential while maintaining the eigenvalue spectrum and logarithmic derivatives. Recent work 22,26,27 has shown that this approach yields highly accurate Hartre-Fock pseudopotentials.…”
Section: Recently Wu Et Al (Wsc)mentioning
confidence: 99%
“…27. The Ga and In pseudopotentials were obtained from scalar-relativistic solutions, while the N pseudopotential was non-relativistic.…”
Section: Recently Wu Et Al (Wsc)mentioning
confidence: 99%
“…The Hartree-Fock approximation was used and the non-analytic behaviour of HF pseudopotentials was treated using the localization and optimization scheme of Al-Saidi, Walter and Rappe 47 . Including exchange exactly in the pseudopotentials is required to ensure accurate core-valence interaction within the current formalism.…”
Section: -39mentioning
confidence: 99%
“…By using Eq. (B1) and a method similar to that described by Al-Saidi and co-workers 83 to generate a norm-conserving screened pseudopotential V aPS (r), we can then use a similar unscreening process described by Eq. (47) to determine a suitableṼ a loc (r) for each atom.…”
Section: Discussionmentioning
confidence: 99%
“…This extension of ideas presented in the original PAW formalism 38 was first introduced by Paier and co-workers. 4 In principle, the correct treatment of the charge moments in PAW approach should have accuracy advantages over norm-conserving pseudoptential methods 73,74,76,78,83,84 which explicitly control only the diagonal L = 0 pair charges. We also show that the treatment of core effects in the Fock exchange are best implemented in terms of frozencore orbitals which can be accomplished with high accuracy within the PAW method.…”
Section: Discussionmentioning
confidence: 99%